Mohammad Sjafei: A Nationalist Educator in West Sumatra - Wati, Listia Anita; Rochwulaningsih, Yety; Puguh, Dhanang Respati (Indonesian Historical Studies, 2024)
This article discusses Mohammad Sjafei's nationalist thoughts in the fields of politics and education from 1914 to 1958. This research uses historical methods. The article contains a description of how the educational system under the Ethical Policy program provided opportunities for the rise of nationalism among the indigenous people. The expansion of education encouraged openness of mind and knowledge among the indigenous population. This process of nationalist awakening stimulated the emergence of national thinkers who played a role in the struggle during the movement era. The role and contribution of these national thinkers are important to study in order to enhance understanding and knowledge in the field of intellectual history. One such national thinker examined in this article is Mohammad Sjafei. He was a national education figure who had nationalist thoughts in the fields of politics and education. His nationalist thoughts in politics encompassed values of unity, national loyalty, and love for the nation. His nationalist thoughts in education emphasized the importance of forming the nation’s identity and promoting education that is Indonesiacentric. Sjafei implemented these two nationalist thoughts in his educational practices at Indonesisch Nederlandsche School Kayutanam. The school was used as a medium to disseminate nationalistic awareness, sharpen intellectual intelligence, and develop skills.